The unfinished nation : - Brinkley, Alan (McGraw-Hill, 2004)
The book presents a balanced picture that connects the newer histories of society and culture with the more traditional stories of politics, diplomacy, and great public events and individuals. In this new fourth edition, Brinkley continues to focus on the whole story of America's history by incorporating new coverage of environmental history, science and technology, and America within a blobal context.